Implications of Information Load on Fiscal Decentralization Delivery in Government Aided Primary Schools in Uganda - Munulo, Kato Hussein; Kagambirwe, Karyeija Gerald (Public Policy and Administration Research, 2019)
The study explores the importance of information load in enhancing Fiscal Decentralization delivery in Government Aided Primary Schools in Busoga sub region, Eastern Uganda. The study is occasioned by availability of not so many empirical studies in many developing countries such as Uganda. The major objectives of this study are to establish the relationship between information load and Fiscal Decentralization in Busoga Sub region Government Aided Primary Schools in eastern Uganda. Methodology: This study adopted a cross sectional design under a quantitative and qualitative methods. Data collection was done on a sample of 314, respondents. The data was analyzed using multiple regression and confirmatory factor analysis using Amos. Findings: The findings of the study indicate that the association is positive and significant which means the information load improves Fiscal Decentralization delivery. Unique contribution to the theory, practice and policy: It is therefore noted that many public schools face significant challenges in the management of fiscal resources, as such it is recommended that the Central Government streamlines communication and availability of information to the lowest accounting officers (Headteachers), such that there is prompt information availability in form of circulars using traditional media, organize regional meetings/workshops to disseminate information every quarter on release of funds to government institutions.
Keywords: Fiscal decentralization delivery; Information load; Lowest accounting officers; Government aided primary schools